1998
DOI: 10.1017/s0960258500004475
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of seed dormancy and germination in an annual and a perennial species of Senna (Fabaceae)

Abstract: 1998). A comparative study of seed dormancy and germination in an annual and a perennial species AbstractSeed dormancy and germination of Senna marilandica and S. obtusifolia were compared in greenhouse and laboratory studies. About 90% of the S. obtusifolia seeds were green and had hard seed coat dormancy, whereas the other 10% were brown and nondormant. Seed-colour morphs did not occur in S. marilandica, and nearly 100% of the seeds had hard seed coat dormancy. Seeds of S. obtusifolia were significantly heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
40
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 29 publications
9
40
0
6
Order By: Relevance
“…Different seed scarifi cation methods have been documented for Mimosa species (De Souza-Araújo and De Castro-Andrade, 1983; Camargo-Ricalde and Grether, 1998;Martínez-Pérez et al, 2006;Silveira and Fernandes, 2006 In this study, mechanically scarifi ed seeds reached high germination percentages (over 70 %) for both taxa; while, unscarifi ed seeds only achieved 0-12 %. In nature, even if seed germination is low, Mimosa seed scarifi cation occurs by different mechanisms such as changes in daily temperature, incomplete predation by insects as bruchids (Orozco-Almanza et al, 2003;Camargo-Ricalde et al, 2004), damage caused by soil microorganisms, abrasion by soil particles and fi re (Baskin et al, 1998;Taylor, 2005), and animal ingestion (i.e. goats, Baraza and Valiente-Banuet, 2008;Giordani, 2008).…”
Section: Effect Of Seed Scarifi Cation On Germinationmentioning
confidence: 99%
“…Different seed scarifi cation methods have been documented for Mimosa species (De Souza-Araújo and De Castro-Andrade, 1983; Camargo-Ricalde and Grether, 1998;Martínez-Pérez et al, 2006;Silveira and Fernandes, 2006 In this study, mechanically scarifi ed seeds reached high germination percentages (over 70 %) for both taxa; while, unscarifi ed seeds only achieved 0-12 %. In nature, even if seed germination is low, Mimosa seed scarifi cation occurs by different mechanisms such as changes in daily temperature, incomplete predation by insects as bruchids (Orozco-Almanza et al, 2003;Camargo-Ricalde et al, 2004), damage caused by soil microorganisms, abrasion by soil particles and fi re (Baskin et al, 1998;Taylor, 2005), and animal ingestion (i.e. goats, Baraza and Valiente-Banuet, 2008;Giordani, 2008).…”
Section: Effect Of Seed Scarifi Cation On Germinationmentioning
confidence: 99%
“…Whilst the summer temperature and diurnal temperature fluctuations in tropics are known to act as important cues in breaking dormancy (Hagon 1971;Jayasuriya et al 2008;McDonald 2000;Moreno-Casasola et al 1994;Quinlivan 1968;Renzi et al 2016), the factors that make seeds permeable in temperate and moist environment are less well known. Although burial experiments in temperate ecosystems indicated that PY seeds use winter temperature to break dormancy (probably during winter) and germinate in spring (Van Assche et al 2003), some studies showed that temperature prevailing in these ecosystems do not break dormancy (Baskin et al 1998). Despite this, the moisture content of seeds in those studies was not determined, thus limiting our ability to draw more apparent conclusion (Jaganathan 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Za prekidanje mirovanja semena mogu se koristiti različite metode, kao što su: -držanje semena u suvim skladištima [15]; -izlaganje semena niskim temperaturama (3-6 o C) nekoliko dana, a potom optimalnim temperaturama za klijanje [16]; -izlaganje semena visokim temperaturama (30)(31)(32)(33)(34)(35) o C) u trajanju od nekoliko dana pre izlaganja delovanju optimalne temperature za klijanje [17,18]; -prekid mirovanja se postiže držanjem semena na svetlosti, pri čemu se obično kombinuje svetlost i temperatura u cilju prekida mirovanja semena [19]; -podvrgavanje semena uticaju različitih hemijskih sredstava kao što su: regulatori rasta, oksidanti, biljni produkti, azotna jedinjenja i druga hemijska sredstva [20,21]; -povređivanjem (skarifikacija) semena se može postići prekid mirovanja kod semena sa tvrdom, za vodu i gasove, nepropustljivom semenjačom (Daucus carota, Hibiscus trionum L., kao i mnoge leguminoze) [20,22]. Mnogi naučnici su radili na otkrivanju metoda za utvrđivanje vrste dormantnosti semena.Ukoliko semena ne klijaju pod optimalnimuslovima za klijanje date vrste, semena se smatraju dormantnim i sledeći korakje da se odredi vrsta mirovanja.…”
Section: Metode Za Prekidanje Mirovanja Semena Korovskih Biljakaunclassified